(untitled) (Fiep Bulletin - online, 2014)
The increase of pregnancy in adolescence in developing countries has aroused the interest of researchers and health professionals, with a view to the combination of this event with poverty, low education and worse perinatal outcomes. This is a public health problem both in Brazil and in many other countries of the world. To understand the possible risk factors associated with the increase in pregnancies in this age group, you need to understand the complexity and the multi-casualty these factors, which make young people especially vulnerable to this. This study aimed to review, in the database Thesis Tapes, the factors of risk for pregnancy in adolescence. This is a study of the literature review conducted in the database Thesis Capes until junho/2006, being used as a descriptor pregnancy in adolescence and found 215 productions science. Used as a criterion for inclusion in the review research that focused the factors of risk for pregnancy in adolescence, were selected 71 scholarly works, of which, 87.3% and 12.7% of Masters of PhD. the socio-family troubled (22.5%), pregnancy is unplanned (19.7%), discontinuation of the contraceptive methods (19.7%), union consensual (15.5%) and wish to have a child with 14, 1%. We can see that in the studies examined are many factors that are associated with pregnancy in adolescence and is closely related to socioeconomic conditions, educational, early onset of sexual life, ignorance and inadequate use of contraceptive methods, which are reinforced by the inadequacy of sex education in schools and programs of family planning in the public health services.